Data quantitative and qualitative study in Brazilian Open Data Portals - do Carmo, Shirlei L. O.; Geyer, Claudio F. R.; dos Anjos, Julio C. S. (Journal of Internet Services and Applications, 2024)
Open data is a concept attributed to sharing data with anyone, and in addition to being accessed, this data can be manipulated and redistributed. The optimized and interchangeable use of open data can lead to so-called open innovation, which can be understood as the crossing of information between different organizations, to generate more complete and innovative systems and solutions. Despite the clear benefit for society, there are major challenges highlighted in different studies for its implementation, such as the lack of promotion of open data, the lack of standardization in data availability, as well as the lack of complete and updated information, among others. This study uses an available reproducible methodology, to show, through different dimensions, the open data panorama in Brazil, which indicates that there are many opportunities for improvement, in categories such as standardization of data exposure and its licenses, update rate, and, due to the absence of some data, the lack of promotion of open data.